Pragmatic dimensions in parable research and the divine economy of the basileia - Andries G. van Aarde (HTS Teologiese Studies/Theological Studies, 2014)
Interpreting a parable requires the decoding of the nature of an analogy which will reveal the degree of the deciphering of the riddle communicated through parabolic discourse. In biblical hermeneutics throughout the 20th century Aristotelian logic revived in parable research in that the nature of a ‘meta-phor’ between the subject and the predicate in a comparison (the so-called Ähnlichkeitsrelation) was understood in terms of either ‘epi-phor’ (analogy) or ‘dia-phor’ (disanalogy). This distinction contributes to the disclosure of power relationships concealed in religious discourse by uncovering the subversive dimension of parabolic discourse. This article focuses on aspects from pragmatic linguistics (especially the role of implicature in communication) and antisociety language usage. These two aspects are explained by illustrations from the Jesus tradition (parable of the pearl), Epictetus’s dissertations (meal parable), and Paul’s comments on marriage (1 Cor 7).